Application of SiC particles coated with a protective Ni layer for production of Ni/SiC co-electrodeposited composite coatings with enhanced tribological properties. Issue 17 (1st December 2019) - Jenczyk, Piotr; Gawrońska, Małgorzata; Dera, Wojciech; Chrzanowska-Giżyńska, Justyna; Denis, Piotr; Jarząbek, Dariusz M.
Abstract: In this paper, the mechanical properties of composites consisting of electroplated Ni and co-electrodeposited SiC particles, coated with a thin protective layer of Ni, were studied. The protective layer was on the SiC particles prior to adding them to the electrolyte bath. It was demonstrated that due to the application of the protective layer it was possible to decrease sliding friction force, and improve the wear resistance, of the composite coatings in comparison with standard electroplated composite coatings made of Ni and co-electrodeposited pure SiC particles. Coating SiC particles with Ni was achieved by means of a PVD process. The main advantage of this step is avoiding oxidation of the surface of the particles during the contact with an electrolyte. Particles protected from oxidation lead to stronger interfacial bonding between the matrix and the reinforcement. Furthermore, better bonding protects the SiC particles from being extracted from the matrix by a counter-probe during friction and wear tests. The influence of the particle's concentration is studied. A smaller friction force and constant wear rate was observed.